Scrutinizing the Embrace of Human Rights in Ugandan Prisons: An Ethnographic Analysis of the Equivocal Responses to Human Rights Watch Reporting. (7th August 2017) - Martin, Tomas Max
Abstract: An acclaimed human rights reform process seems to change Ugandan prisons according to policy prescriptions. Yet prison officers continue to bend rules and use physical violence to actually ensure custodial control and survive professionally in situations of insecurity and exigency. An external audit by Human Rights Watch systematically reads this pragmatic appropriation of human rights as duplicitous and deviant, while the prison management takes the external criticism as an opportunity to reconsolidate itself as a human rights observer in the charged debate about reform. It is thereby argued that human rights take effect in Ugandan prisons as a form of governance that invigorates bureaucratic power and enables institutional reproduction.